1992
DOI: 10.2514/3.11514
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic evaluation of damage characteristics in a composite solid propellant

Abstract: This paper summarizes the current progress in characterizing the damage field near the tip of a crack in a composite solid propellant, using the acoustic-imaging technique. The effects of loading history on the damage characteristics near the crack tips are discussed. In addition, the limitations of the acoustic-imaging technique are discussed, and recommendations for future work are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…used acoustic emission technology to test the uniaxial tensile process of HTPB after temperature impact (alternating ambient temperature), and found that the time when the damage threshold occurred was earlier. From this, it was inferred that the propellant after temperature impact was more prone to initial damage under external load, and derived the linear relationship between the cumulative energy of acoustic emission of propellant and crack growth [37]. Chang et al.…”
Section: Macro Scale Dewetting Experiments and Analysis Methodsmentioning
confidence: 99%
“…used acoustic emission technology to test the uniaxial tensile process of HTPB after temperature impact (alternating ambient temperature), and found that the time when the damage threshold occurred was earlier. From this, it was inferred that the propellant after temperature impact was more prone to initial damage under external load, and derived the linear relationship between the cumulative energy of acoustic emission of propellant and crack growth [37]. Chang et al.…”
Section: Macro Scale Dewetting Experiments and Analysis Methodsmentioning
confidence: 99%
“…For highly filled elastomeric materials containing 200 mm particles the damage characteristics on the mesoscale were investigated, using nondestructive testing techniques [5][6][7][8][9]. The importance of these studies stems from the fact that damage on the mesoscale can significantly affect the macro constitutive and crack growth behavior in these materials.…”
Section: Introductionmentioning
confidence: 99%